Corn starch (Zea mays) biopolymer plastic reaction in combination with sorbitol and glycerol - Md Damiri, Mohamad Hazrol; Salit, Mohd Sapuan; Zainudin, Edi Syams; Mohamed Yusoff, Mohd Zuhri; Abdul Wahab, Noor Izzri (Multidisciplinary Digital Publishing Institute, 2021)
The research included corn starch (CS) films using sorbitol (S), glycerol (G), and their combination (SG) as plasticizers at 30, 45, and 60 wt %, with a traditional solution casting technique. The introduction of plasticizer to CS film-forming solutions led to solving the fragility and brittleness of CS films. The increased concentration of plasticizers contributed to an improvement in film thickness, weight, and humidity. Conversely, plasticized films reduced their density and water absorption, with increasing plasticizer concentrations. The increase in the amount of the plasticizer from 30 to 60% showed a lower impact on the moisture content and water absorption of S-plasticized films. The S30-plasticized films also showed outstanding mechanical properties with 13.62 MPa and 495.97 MPa, for tensile stress and tensile modulus, respectively. Glycerol and-sorbitol/glycerol plasticizer (G and SG) films showed higher moisture content and water absorption relative to S-plasticized films. This study has shown that the amount and type of plasticizers significantly affect the appearances, physical, morphological, and mechanical properties of the corn starch biopolymer plastic.